Upaya Menumbuhkan Stimulus Respon Peserta Didik Melalui Penerapan Teori Belajar Behavioristik - Wahyu Almizri; Neviyarni S (Journal of Pedagogy and Online Learning, 2022)
Abstract: The purpose of this study is to describe the applications and benefits used by teachers in stimulating student stimulus responses through behavioristic theory. This research method using literature study. The data collection tool used is through searching scientific journals that I took from several electronic media. The data analysis technique used in this study is annotated bibliography analysis. This research boils down to the conclusion that the teacher in applying behavioristic theory to stimulate student response stimulus is that the teacher must understand the differences in student learning styles and their respective characteristics, the readiness of students to learn must also be considered by the teacher, and the teacher provides good modeling/imitation to students. Keywords: behavioristic theory, learning style